Protein solvation in allosteric regulation: A water effect on hemoglobin - Colombo, Marcio F. [UNESP]; Rau, Donald C.; Parsegian, V. Adrian (American Association for the Advancement of Science (AAAS), 1992)
The oxygen affinity of hemoglobin varies linearly with the chemical potential of water in the bathing medium, as seen from the osmotic effect of several neutral solutes, namely sucrose, stachyose, and two polyethyleneglycols (molecular weights of 150 and 400). The data, analyzed either by Wyman linkage equations or by Gibbs-Duhem relations, show that -60 extra water molecules bind to hemoglobin during the transition from the fully deoxygenated tense (T) state to the fully oxygenated relaxed (R) state. This number, independent of the nature of the solute, agrees with the difference in water-accessible surface areas previously computed for the two conformations. The work of solvation in allosteric regulation can no longer go unrecognized.